Carlotta Gall, The Wrong Enemy: America in Afghanistan 2001-2014 - Mr. Majid Mahmood (CISS Insight Journal, 2014)
In The Wrong Enemy: America in Afghanistan 2001-2014 Carlotta Gall argues that Pakistan is responsible for the resurgence of Taliban resistance post 2001 and negatively impacted US war strategy in Afghanistan. In her opinion, the patronage and protection that Taliban movement enjoyed within Pakistan after their retreat from Afghanistan was not coincidental but a matter of policy by the Pakistan army.The book is a narrative about the conditions, resources and methods used by the Taliban to stage a comeback within few years after their defeat in 2001. It also narrates how the local, regional and global developments helped the insurgency in maintaining its momentum against the Western forces. The title of the book “The Wrong Enemy” is a quotation from Richard C. Holbrooke, the United States special representative to Afghanistan and Pakistan, who said: “We may be fighting the wrong enemy in the wrong country.”As a part of her job as a reporter with daily New York Times, Carlotta Gall was able to observe the conflict and insurgency in Afghanistan at the local and regional levels by going into the field. She was able to travel in the pro-Taliban villages extensively, mainly in Southern Afghanistan, to study the insurgency’s main support base. Looking at the situation at the local level, Gall addresses and explains how poor governance in Afghanistan, local grievances of Pushtun tribes, Islamic influence, civilian casualties caused by US raids and their support for Afghan militias, resulted in creating the support base for the Taliban.